Student Perception Regarding the Use of Sarcasm in Classroom Interaction in the University Context - Sunusi, Seny Luhriyani; Taswadi, Muh. Qayyum; Korompot, Chairil Anwar; Sakkir, Geminastiti (Har Press Indonesia, 2025)
This research aimed to identify in what types of interaction patterns sarcasm is found in the classroom and what students' perceptions regarding the use of sarcasm in classroom interactions. This research used qualitative methods to obtain data from respondents. The respondents in this research were lecturers who use English when teaching and students who are familiar with sarcasm. The results obtained from this research show that sarcasm is found in three interaction patterns, namely one-way interaction, two-way interaction, and multidirectional interaction. Meanwhile, students' perceptions regarding sarcasm have pros and cons. There are those who think sarcasm is appropriate in the classroom. It can trigger laughter and others who think it is inappropriate because it can hurt someone's feelings.